The conservation of aesthetical values in traditional design for JKKN Makyung costumes in Kelantan based on its sociocultural system - Zolkipli Abdullah (Tanjong Malim, 2021)
The conservation of aesthetical values in traditional design for JKKN Makyung costumes in Kelantan based on its sociocultural system by Zolkipli Abdullah